INVESTMENTS IN TECHNOLOGIES OF THE AGRICULTURAL SECTOR - M.A. Kassimbekova; Z.S. Mukhambetova; M.N. Nurgabylov; K.N.Tastanbekova; A. Blyalova; D.T. Zhumanova (Academic Journal of Physical and Chemical Sciences, 2019)
The agricultural sector of Kazakhstan has enormous potential for further increase in production, provided that appropriate investments are attracted and advanced technologies and scientific achievements are introduced. The economic mechanism is a complex system, which in our understanding is considered as part of the economic mechanism and as a form of organizational and economic relations. Its essence is to establish optimal ratios of various methods and levers, including price and financial-credit mechanisms, insurance and taxes, budget support and investment in the agricultural sector.